The Bitter Side of Sweetness: Glycation as the Silent Driver of Aging - Banavath, Vijay Kumar Naik; Naveen, Udara; Soheb, Shaik Muhammad; Masood, Shaik Ontela (Journal of Pharmacy Practice and Community Medicine)
Aging is a progressive decline in physiological function characterized by the accumulation of biochemical waste such as Advanced Glycation End products (AGEs). Sugar glycation, a nonenzymatic reaction between reducing sugars and biomolecules like proteins, DNA, and lipids, produces AGEs that impair structural integrity and cellular communication. This review explores the mechanisms by which AGEs accelerate cellular and tissue aging, emphasizing their roles in oxidative stress, inflammation, and metabolic dysfunction. Elevated AGE levels, whether formed endogenously under hyperglycemic conditions or ingested through heat-processed foods, contribute to diabetic complications, cardiovascular diseases, neurodegeneration, and loss of tissue elasticity. Evidence suggests that glycation and oxidative stress share a molecular foundation linking aging and metabolic disorders and also evaluates existing evidence on interventions including dietary AGE restriction, antioxidant therapy, and lifestyle modification to mitigate glycation-induced damage. Advanced glycation end products are key mediators of aging and age-related diseases. Collectively, the findings suggest that aging and diabetes share a molecular basis in oxidative and glycative stress, and that modulating these pathways can extend health span and delay age-related disease progression.
Keywords: Advanced Glycation End Products; Aging; Metabolic Waste Accumulation; Nonenzymatic Reaction; Reactive Oxygen Species; Receptor for Ages